Pilot intervention in an economically disadvantaged community: The back‐to‐basics after‐school healthy lifestyle program. Issue 4 (29th January 2013) - Burrows, Tracy; Bray, James; Morgan, Philip J.; Collins, Clare
Abstract Aim The objective of the present study was to assess the feasibility and acceptability of an after‐school obesity prevention strategy for families. Methods Ten children aged 5–12 years and their parents/guardians from an economically disadvantaged area participated in an after‐school healthy lifestyle program, which was run over a school term. It consisted of five face‐to‐face sessions that were run fortnightly with an additional social barbeque session at program completion. Results Feasibility was demonstrated by successful recruitment, retention (80%) and collection of a high percentage of usable data (96% at baseline, 80% at follow up). Acceptability was demonstrated by a session attendance of 83%, 100% positive enjoyment response. There was no significant change in anthropometrics, child or adult fruit and vegetable intake with no or little effect on all other dietary variables. Conclusions The present study illustrated an approach to the translation of a program used in an evidence‐based efficacious clinical trial into a sustainable community setting.